DOI: 10.31274/etd-180810-5027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of workers' compensation claims data for improving safety outcomes in agribusiness industries

Abstract: for serving on my program of study committee and for their help and guidance throughout this project. I thank the mid-west based insurance company for their help with the data used in this study. I thank my fellow graduate students,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Our results showed that the proportion of serious claims increased with the increase of age. Moreover, a 1-year increase in age was associated with a 3.7% and 1.3% increase of compensation expenditure and working time lost, respectively, indicating that older workers sustained more severe injuries than their younger counterparts and required more days away from work to recover [35,40,41]. Schwatka et al attributed this to older workers' selectively reporting serious injuries due to worries of negative attention for their carelessness or unsafe behaviours [42].…”
Section: Injury Severity: Growing Challenges Of An Aging Labour Forcementioning
confidence: 99%
“…Our results showed that the proportion of serious claims increased with the increase of age. Moreover, a 1-year increase in age was associated with a 3.7% and 1.3% increase of compensation expenditure and working time lost, respectively, indicating that older workers sustained more severe injuries than their younger counterparts and required more days away from work to recover [35,40,41]. Schwatka et al attributed this to older workers' selectively reporting serious injuries due to worries of negative attention for their carelessness or unsafe behaviours [42].…”
Section: Injury Severity: Growing Challenges Of An Aging Labour Forcementioning
confidence: 99%
“…Further, existing literature that has used WC data to estimate associated payments has been limited in scope with regards to sample size, states included, limited injury characteristics analyzed individually, etc. [ 8 , 9 , 10 , 11 ]. This research effort uses data from a large insurance program covering several years and all fifty states to provide estimates for WC payments across specific injury characteristics related categories, stratified by the claim severity.…”
Section: Introductionmentioning
confidence: 99%